The Diplomatic Asylum: From Haya De La Torre to The "WikiLeaks" Case - Vázquez, Agustina (2018)
The WikiLeaks’ founder represents not only a challenge to freedom of information, but also to International Law related to the diplomatic asylum. Julian Assange has been living in the Ecuadorian embassy in London for five years. In the last weeks, news surfaced that Sweden has ceased to request his extradition, the fact that caused much of the case under study. Assange’s situation seems to be diametrically different from Edward Snowden’s; however, both are labeled as "refugees for political reasons". While Assange looks forward to an improvement in his situation in the Ecuadorian embassy in London, Snowden still lives in Russia. Is the diplomatic asylum a usual practice? How to understand the diplomatic asylum in Latin America? What about England? In this paper, the analysis will assume that the concept of asylum is not recognized as a universal practice of International Law. However, in Latin America, it seems to be a usual practice since the judgment of the International Court of Justice on Haya de la Torre’s case.